Integrating Pancasila (Religious-Humanist- Nationalist-Democratic-Caring) Values in Learning at the High School Level - Kardiman, Yuyus; Rudi Casmana, Asep; ., Sapriya; Camelyn Sinaga, Irene (KnE Social Sciences, 2024)
This study aims to develop learning models and methods by integrating the basic concepts of Pancasila values. Religious-humanist-nationalist-democratic-caring, hereinafter abbreviated as RHNDP in every learning at the high school level. The research method used is research and development, using several main procedures, including; 1) initial information collection; 2) planning; 3) initial product development; 4) initial trials; 5) product revision); 6) field trials; and 7) product revision. The research was designed for 3 years, where in the first year, the first program was carried out, namely the collection of data or initial information. Data collection techniques were carried out through observation, interviews with 7 (seven) high schools from DKI Jakarta and the city of Bandung, questionnaires and literature reviews. The results of the study found that the basic problems in the field are 1) the perception that Pancasila learning seems to be only the task of Pancasila Education teachers. 2) There has not been an integration of RHNDP Pancasila values in every lesson, less than 10% of teachers interviewed have integrated RHNDP values in learning, while more than 90% of teachers have taught concepts in subjects, without integrating RHNDP values as basic values of life. 3) Learning RHNDP values is carried out only through habituation without involving elements of knowledge and concepts in each subject. For this reason, it is important to develop learning models and methods to integrate the values of RHNDP Pancasila in learning. Keywords: integrating, religious-humanist-nationalist-democratic-caring, learning